2024
DOI: 10.1038/s41598-024-56796-7
|View full text |Cite
|
Sign up to set email alerts
|

The association between platelet-related parameters and nonalcoholic fatty liver disease in a metabolically healthy nonobese population

Eun Kyung Choe,
Hae Yeon Kang

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease characterized by subclinical inflammation and is related to obesity and metabolic syndrome (MS), but it is also frequently observed in nonobese populations. We aimed to evaluate the relationship between the white blood cell count-to-mean platelet volume ratio (WBC/MPV), platelet-to-lymphocyte count ratio (PLR) and lymphocyte-monocyte ratio (LMR) in association with NAFLD, considering the presence of obesity and MS. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
1
0
0
Order By: Relevance
“…Interestingly, our observations revealed that PLR exhibited higher diagnostic accuracy for NAFLD among the non-diabetic population compared to the diabetic population (AUCROC=0.804/AUCROC=0.762). Additionally, PLR was found to be associated with NAFLD specifically within the non-obese population ( 25 ), aligning with the observation ( 26 ) that the risk of detecting NAFLD in patients with obstructive sleep apnea–hypopnea syndrome via PLR was more favorable in those with a BMI <28 kg/m². This suggests that the non-metabolic disorders population may be more appropriate for the application of PLR.…”
Section: Discussionsupporting
confidence: 75%
“…Interestingly, our observations revealed that PLR exhibited higher diagnostic accuracy for NAFLD among the non-diabetic population compared to the diabetic population (AUCROC=0.804/AUCROC=0.762). Additionally, PLR was found to be associated with NAFLD specifically within the non-obese population ( 25 ), aligning with the observation ( 26 ) that the risk of detecting NAFLD in patients with obstructive sleep apnea–hypopnea syndrome via PLR was more favorable in those with a BMI <28 kg/m². This suggests that the non-metabolic disorders population may be more appropriate for the application of PLR.…”
Section: Discussionsupporting
confidence: 75%